Nitrogen-doped carbon nanosphere-molybdenum carbide-carbon nanotube composite material, preparation method thereof and application of nitrogen-doped carbon nanosphere-molybdenum carbide-carbon nanotube composite material in hydrogen evolution by water electrolysis

Through the interaction of phosphomolybdate and dopamine and the grinding with melamine, a one-step calcination method is used to prepare nitrogen-doped carbon nanospheres @molybdenum carbide @carbon nanotube composite materials, which solves the problem of cumbersome and high cost of preparation methods for the existing electrolytic hydrogen analysis catalysts, and achieves efficient and stable electrocatalytic performance.

CN119800432AActive Publication Date: 2025-04-11HEBEI UNIVERSITY

Patent Information

Application Number
CN202510281794.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-11
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

The existing preparation methods for electrolytic hydrogen analysis catalysts are cumbersome, the reaction conditions are harsh and the cost is high, which limits its large-scale application.

Method used

Using the interaction of phosphomolybdate and dopamine, a polydopamine-phosphomolybdate-melamine composite is obtained through simple grinding with melamine, followed by calcination to achieve carbonization of polydopamine and melamine, molybdenum and nitrogen doping, and nitrogen-doped carbon nanospheres @molybdenum carbide @carbon nanotube composite material.

Benefits of technology

The preparation process is simplified, cost is reduced, and the morphological uniformity and electrocatalytic properties of the material are improved, showing a smaller taffel slope, higher capacitance and higher stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800432A_ABST
    Figure CN119800432A_ABST
Patent Text Reader

Abstract

The invention provides a nitrogen-doped carbon nanosphere-molybdenum carbide-carbon nanotube composite material and a preparation method and application thereof in hydrogen evolution by electrolysis of water, the preparation method comprises the following steps: combining phosphomolybdic acid with dopamine through interaction, grinding with melamine to fully mix, and finally calcining in one step to obtain the nitrogen-doped carbon nanosphere-molybdenum carbide-carbon nanotube composite material. The nitrogen-doped carbon nanosphere-molybdenum carbide-carbon nanotube composite material is prepared by the following steps of: carbonizing polydopamine and melamine and doping nitrogen and molybdenum, catalyzing molybdenum to generate a carbon nanotube, and finally obtaining the nitrogen-doped carbon nanosphere-molybdenum carbide-carbon nanotube composite material, and applying the nitrogen-doped carbon nanosphere-molybdenum carbide-carbon nanotube composite material to the catalytic research of hydrogen evolution reaction by electrolysis of water. Compared with the traditional preparation method, the method disclosed by the invention is simple, rapid, mild in reaction condition and high in yield, and the prepared composite material is uniform in morphology and has excellent electro-catalytic performance on a water electrolysis hydrogen evolution reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen evolution catalysis by water electrolysis, and in particular to a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material and a preparation method thereof and application thereof in hydrogen evolution by water electrolysis. Background Art

[0002] Hydrogen-powered vehicles are a new type of energy vehicle that requires a large amount of hydrogen as fuel. Currently, the preparation of molecular hydrogen is usually done through water decomposition reaction (H 2 O→H 2 +O 2 ) is achieved. Electrochemical water splitting has become one of the important ways to produce hydrogen due to its high hydrogen evolution efficiency and easy industrialization. However, the reaction rate of electrochemical water splitting is slow and requires a high overpotential. Therefore, it is often necessary to seek electrochemical water splitting hydrogen evolution catalysts to increase the reaction rate.

[0003] For hydrogen evolution catalysts from water electrolysis, the most efficient ones are noble metal-based catalysts, such as Pt, Ru and Ir. Metallic Pt is considered to be the best electrocatalyst for hydrogen evolution reaction, showing a near-zero starting potential. However, the scarcity, high cost and poor durability of Pt limit its large-scale application. Transition metals (including iron, cobalt, nickel, copper, molybdenum, tungsten, etc.) are abundant in the earth's crust, are cheap, environmentally friendly, have unfilled d electron orbitals, have variable valence states, and can easily form different types of complexes, making them efficient substitutes for noble metals.

[0004] Carbon nanomaterials have excellent electrical conductivity, high specific surface area, and are easy to control. Graphene, carbon nanofibers, and carbon nanotubes are widely used as electrocatalyst carriers to load transition metals. In the field of hydrogen evolution by electrolysis of water (HER), some excellent work has been done. Some researchers have prepared CoFc-(MOF) by phosphating the precursor x P-FeP@C catalyst. Optimized Co 2 P-FeP@C-5 for HER with a current density of 10 mA cm -2 The overpotential is 169 mV. Some researchers have prepared a self-supporting ultra-thin carbon layer of bimetallic phosphide bonded to iron foam (C@CoP-FeP / FF), and in a simulated overall seawater decomposition experiment, a current density of 10 mA cm -2 The overpotential is 173 V, and it maintains good stability within 100 hours. These carbon-transition metal materials have excellent performance in hydrogen evolution by electrolysis of water, but the material preparation method is cumbersome, the reaction conditions are harsh, the cost is high, and it is not convenient for large-scale promotion and application. Summary of the invention

[0005] The purpose of the present invention is to provide a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material and its preparation method and application in water electrolysis and hydrogen evolution, so as to solve the problems of complicated steps, harsh reaction conditions and high preparation cost of the existing preparation method.

[0006] The object of the present invention is achieved in that: A method for preparing a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material comprises the following steps: (1) Dissolve phosphomolybdic acid in water, then add tris(hydroxymethyl)aminomethane and stir thoroughly; (2) After ultrasonically mixing the solution obtained in step (1) to be uniformly mixed, dopamine is added, and the mixture is fully stirred in a dark environment at room temperature, followed by centrifugation, washing, and drying; the mass ratio of the added dopamine to the phosphomolybdic acid in step (1) is 5:44-176; (3) Grinding melamine and the product obtained in step (2) to obtain a precursor powder; the mass ratio of melamine to dopamine in step (2) is 2:5; (4) Calcining the precursor powder obtained in step (3) under an inert atmosphere to obtain a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material.

[0007] Preferably, in step (4), the precursor powder is calcined under an inert atmosphere, specifically: the precursor powder is heated to 550° C. and calcined for 3 h, and then heated to 900° C. and calcined for 3.5 h.

[0008] Preferably, in step (2), the mass ratio of the added dopamine to the phosphomolybdic acid in step (1) is 5:176.

[0009] Preferably, in step (2), the ultrasonic treatment time is 30 min, the ultrasonic power is 350 W, the drying temperature is 60° C., and the drying time is 12 h.

[0010] In the step (2), dopamine is used as the carbon source, nitrogen source and linker, and the centrifugal speed is 9000 r / min.

[0011] In the step (3), melamine also serves as a carbon source and a nitrogen source.

[0012] In the step (4), the heating rate is 5°C / min.

[0013] The present invention also provides an application method of the obtained nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material, which comprises dispersing the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material into a dispersant to obtain a dispersion liquid, applying the dispersion liquid droplets on the surface of a glassy carbon electrode, and drying at room temperature to be used for a hydrogen evolution reaction, wherein the dispersant is a naphthol solution.

[0014] The present invention combines phosphomolybdic acid with dopamine through the interaction between phosphomolybdic acid and dopamine, and then simply grinds with melamine to fully mix them to obtain a polydopamine-phosphomolybdic acid-melamine complex. Finally, through a one-step calcination, carbonization of polydopamine and melamine, doping of molybdenum and nitrogen are simultaneously achieved, and molybdenum can catalyze the generation of carbon nanotubes, and finally a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material is obtained.

[0015] Compared with the prior art, the synthesis method of the present invention is simple, rapid, environmentally friendly, has high yield, mild reaction and low cost. The nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material prepared by the method of the present invention has uniform morphology, realizes nitrogen-molybdenum co-doping, and has excellent electrocatalytic performance for hydrogen evolution reaction, which is manifested as a smaller Tafel slope, higher capacitance and higher stability. And as a catalyst, it provides a new choice for research in related fields such as energy storage, conversion, fuel cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the preparation process of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material of the present invention.

[0017] Figure 2 1 is a scanning electron microscope image of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material prepared in Example 1 of the present invention; wherein (A) is a scanning electron microscope image at a scale of 500 nm, and (B) is a scanning electron microscope image at a scale of 200 nm.

[0018] Figure 3 1 is an X-ray photoelectron spectrum of the nitrogen-doped carbon nanosphere @ molybdenum carbide @ carbon nanotube composite material prepared in Example 1 of the present invention; wherein (A) is the overall spectrum of the composite material, (B) is the C1s high-resolution XPS peak spectrum, (C) is the N1s high-resolution XPS peak spectrum, and (D) is the Mo high-resolution XPS peak spectrum.

[0019] Figure 4 1 is an X-ray diffraction diagram of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material prepared in Examples 1 to 3 of the present invention.

[0020] Figure 5 The linear sweep voltammetric polarization curve and the corresponding Tafel slope diagram of the nitrogen-doped carbon nanosphere @ molybdenum carbide @ carbon nanotube composite material prepared in Examples 1 to 3 of the present invention for the hydrogen evolution reaction by electrolysis of water; wherein (A) is the linear sweep voltammetric polarization curve diagram, and (B) is the Tafel slope diagram corresponding to (A).

[0021] Figure 6The present invention is a cyclic voltammogram of the nitrogen-doped carbon nanosphere @ molybdenum carbide @ carbon nanotube composite material prepared in Examples 1 to 3 of the present invention for the electrolysis of water and hydrogen evolution reaction in 1.0M KOH at different scan rates and a linear relationship diagram between the corresponding scan rate and the current density difference; wherein, (A) is a cyclic voltammogram of the composite material prepared in Example 1, (B) is a cyclic voltammogram of the composite material prepared in Example 2, (C) is a cyclic voltammogram of the composite material prepared in Example 3, and (D) is a current density difference Δj (Δj=j a -j c , j a is the anode current, j c Linear fitting plot of cathodic current) and scan rate at a given potential (+0.873 V vs. RHE).

[0022] Figure 7 This is a current density-time curve of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material prepared in Example 1 of the present invention for hydrogen evolution reaction stability test. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with the examples. The processes and methods not described in detail in the following examples are conventional methods well known in the art. Unless otherwise specified, the raw materials or reagents used in the examples are commercially available and can be purchased through commercial channels.

[0024] Example 1 Combination Figure 1 The preparation method of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material provided in this embodiment is as follows: (1) Preparation of polydopamine@phosphomolybdic acid complex 2.20 g phosphomolybdic acid (PMo 12 ) was dissolved in 100 mL of distilled water, and then 37.92 mg of tris(hydroxymethyl)aminomethane (Tris) was added, stirred thoroughly and ultrasonically treated for 30 min (ultrasonic machine power was 350 W), and 62.5 mg of dopamine was added, and stirred for 12 h in a dark environment at room temperature. The obtained product was separated by high-speed centrifugation (9000 r / min), washed three times with deionized water, and then vacuum dried at 60 °C for 12 h to obtain a polydopamine-phosphomolybdic acid complex.

[0025] (2) Preparation of precursor The polydopamine-phosphomolybdic acid complex obtained in step (1) was ground with 25 mg of melamine and mixed thoroughly to obtain a dry precursor powder.

[0026] (3) Preparation of nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composites The precursor powder was heated to 550 °C in a nitrogen atmosphere at a heating rate of 5 °C / min and calcined for 3 h, and then heated to 900 °C and calcined for 3.5 h to obtain a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material.

[0027] Example 2 Compared with Example 1, the PMo used in this example 12 The mass of PMo in Example 1 is 1.10 g 12 The rest is the same as in Example 1 and will not be described in detail.

[0028] Example 3 Compared with Example 1, the PMo used in this example 12 The mass of PMo in Example 1 is 0.55 g 12 1 / 4 of the total), and the rest are the same as those in Example 1 and will not be described in detail.

[0029] The nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite materials prepared in Examples 1 to 3 were characterized. Figure 2-4 shown.

[0030] Figure 2 The scanning electron microscope image of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material prepared in Example 1 is shown. Figure 2 It can be seen that the material morphology is good, and carbon nanospheres and carbon nanotubes are visible.

[0031] Figure 3 The X-ray photoelectron spectroscopy (XPS) of the nitrogen-doped carbon nanosphere @ molybdenum carbide @ carbon nanotube composite material prepared in Example 1 is shown. The valence state and surface chemical properties of the composite material were studied by XPS. Among them, (A) XPS spectrum confirms the presence of C, N, O and Mo in the nitrogen-doped carbon nanosphere @ molybdenum carbide @ carbon nanotube composite material. (B) shows the C 1s high-resolution XPS peak spectrum, in which the peak at 283.9 eV is the characteristic peak of the Mo-C bond, and the peaks at 284.9, 285.6 and 287.5 correspond to C=C / CC, CN and C=O, respectively. (C) shows the N 1s high-resolution XPS peak spectrum, which shows four peaks corresponding to pyridinic N (398.8 eV), pyrrolic N (400.1 eV), graphitic N (402.4 eV) and Mo-N (396.1 eV). (D) shows the Mo 3d high-resolution XPS peak spectrum, the peak with binding energy of 229.3 / 230.5 eV is attributed to Mo 2+ The peaks at 233.9 / 236.9 eV are attributed to Mo 4+The peaks at 232.6 / 235.5 eV are attributed to Mo 6+ , Mo 4+ and Mo 6+ Derived from MoO 2 and MoO 3 Fraction, due to Mo 2 C undergoes inevitable surface oxidation in the air.

[0032] Figure 4 The X-ray diffraction patterns (XRD) of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite materials prepared in Examples 1 to 3 are used to study the composition of the composites. Figure 4 The diffraction peaks of the three materials can be clearly seen, which also proves the presence of C, N, O and Mo elements. Among them, the diffraction peaks at 26.3° and 42.2° correspond to the (002) and (100) crystal planes of graphite carbon (standard card JCPDS 41-14487). The diffraction peaks at 40.5°, 58.6° and 73.6° correspond to the (110), (211) and (220) crystal planes of Mo (standard card JCPDS 42-1120), respectively. The diffraction peaks at 39.3°, 52.1°, 61.5° and 69.5° correspond to the (002), (100) and (110) crystal planes of Mo (standard card JCPDS 42-1120), respectively. 2 C (standard card JCPDS 35-0787) (101), (002), (110) and (103) crystal planes. The diffraction peaks at 37.9° and 45.2° belong to Mo 2 N (standard card JCPDS 24-0768) (112) and (004) crystal planes.

[0033] Electrocatalytic performance test of hydrogen evolution reaction The nitrogen-doped carbon nanospheres@molybdenum carbide@carbon nanotubes prepared in Examples 1 to 3 were applied to the electrocatalysis of hydrogen evolution reaction, and the electrocatalytic performance of the three composite materials was compared. The specific steps are as follows: 1) A three-electrode test system (Autolab 302N electrochemical workstation) was used, with a standard hydrogen electrode (RHE) as the reference electrode, a platinum wire as the counter electrode, a glassy carbon electrode modified with the prepared composite material as the working electrode, and a 1 mol / L potassium hydroxide solution as the electrolyte solution. The preparation method of the working electrode is as follows: 2 mg of the prepared composite material was dispersed in 1 mL of naphthol solution to a concentration of 2 mg / mL, 5 µL of the dispersed solution was applied to the surface of the glassy carbon electrode, and dried at room temperature to obtain a working electrode.

[0034] 2) Place the three electrodes in an electrolytic cell, immerse them in potassium hydroxide solution, select the electrochemical method, set the parameters, and conduct electrochemical testing of the hydrogen evolution reaction.

[0035] Test results see Figure 5-7 . Figure 5 The linear sweep voltammetric polarization curves of the composite materials prepared in Examples 1 to 3 for the hydrogen evolution reaction by electrolysis of water and the corresponding Tafel slope diagrams are shown in FIG. Figure 6 The cyclic voltammetry curves of the composite materials prepared in Examples 1 to 3 for the hydrogen evolution reaction of electrolysis of water in 1.0 M KOH at different scan rates and the linear relationship between the corresponding scan rate and the current density difference are shown. Figure 6 The lines of different colors in (A), (B), and (C) represent different scanning rates. Along the direction indicated by the arrows, the scanning rates corresponding to the lines are 30, 50, 70, 100, 130, 170, 200, 240, 280, and 320 mV / s. Figure 5 and Figure 6 It can be seen that compared with the composite materials prepared in Examples 2 and 3, the composite material prepared in Example 1 has higher electrocatalytic performance for hydrogen evolution reaction, which is manifested by a lower Tafel slope (the Tafel slopes corresponding to Examples 1 to 3 are: 96 mV dec -1 , 126 mV dec -1 , 168 mV dec -1 ), a larger capacitance (the capacitances corresponding to Examples 1 to 3 are 0.1973 mF / cm -2 , 0.1597 mF / cm -2 , 0.1278 mF / cm -2 ).

[0036] Figure 7 is a stability test diagram of the composite material prepared in Example 1 catalyzing the hydrogen evolution reaction at a constant potential of -0.377V. Figure 7 It can be seen that after 24 h of catalytic hydrogen evolution reaction, the current density value only decayed by 8.7%, showing good stability.

[0037] Comparative Example 1: A method for preparing nitrogen-doped carbon nanospheres, comprising the following steps: (1) Dissolve 37.92 mg of Tris in 100 mL of distilled water, stir and ultrasonicate for 30 min (ultrasonicator power is 350 W), add 62.5 mg of dopamine, and stir for 12 h in a dark environment at room temperature. The obtained product is centrifuged at high speed (9000 r / min), washed three times with deionized water, and then dried in vacuum at 60 °C for 12 h to obtain polydopamine.

[0038] (2) Grind and mix the polydopamine obtained in step (1) with 25 mg of melamine to obtain a dry precursor powder.

[0039] (3) The precursor powder obtained in step (2) is heated to 550 °C in a nitrogen atmosphere at a heating rate of 5 °C / min and calcined at 900 °C for 3.5 h to obtain nitrogen-doped carbon nanospheres.

[0040] The Tafel slope of the material obtained in Example 1 for HER is 96 mV dec -1 The Tafel slope of the material obtained in comparative example 1 for HER is 236 mV dec -1 .

[0041] Comparative Example 2: A method for preparing molybdenum carbide@carbon nanotubes, comprising the following steps: (1) 2.20 g PMo 12 Dissolve in 100 mL of distilled water, add 37.92 mg Tris, stir thoroughly and ultrasonicate for 30 min (ultrasonication machine power is 350 W), stir for 12 h in a dark environment at room temperature, centrifuge the obtained product at high speed (9000 r / min), wash it with deionized water for 3 times, and then dry it in vacuum at 60 °C for 12 h.

[0042] (2) The product obtained in step (1) was ground and mixed with 25 mg of melamine to obtain a dry precursor powder.

[0043] (3) The precursor powder in step (2) was heated to 550 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined at 900 °C for 3.5 h to obtain a molybdenum carbide@carbon nanotube composite material.

[0044] The Tafel slope of the material obtained in Example 1 for HER is 96 mV dec -1 The Tafel slope of the material obtained in Comparative Example 2 for HER is 230 mV dec -1 .

[0045] Comparative Example 3 Compared with Example 1, the PMo used in this comparative example 12 The mass of PMo in Example 1 is 4.4 g 12 2 times), the rest are the same as in Example 1 and will not be described in detail.

[0046] The Tafel slope of the material obtained in Example 1 for HER is 96 mV dec -1 The Tafel slope of the material obtained in comparative example 3 for HER is 206 mV dec -1 It is considered that the overlapped aggregation of higher content molybdenum carbide sites may reduce the overall electrocatalytic performance of the composite material to a certain extent.

Claims

1. A method for preparing a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material, characterized in that: The following steps are involved: (1) Dissolve phosphomolybdic acid in water, then add tris(hydroxymethyl)aminomethane and stir thoroughly; (2) After ultrasonically mixing the solution obtained in step (1) to be uniformly mixed, dopamine is added, and the mixture is fully stirred in a dark environment at room temperature, followed by centrifugation, washing, and drying; the mass ratio of the added dopamine to the phosphomolybdic acid in step (1) is 5:44-176; (3) Grinding melamine and the product obtained in step (2) to obtain a precursor powder; the mass ratio of melamine to dopamine in step (2) is 2:5; (4) Calcining the precursor powder obtained in step (3) under an inert atmosphere to obtain a nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material.

2. The method for preparing the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material according to claim 1, characterized in that: In step (4), the precursor powder is calcined in an inert atmosphere, specifically: the precursor powder is heated to 550°C and calcined for 3 h in an inert atmosphere, and then heated to 900°C and calcined for 3.5 h.

3. The method for preparing the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material according to claim 1, characterized in that: In step (2), the mass ratio of the added dopamine to the phosphomolybdic acid in step (1) is 5:

176.

4. The method for preparing the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material according to claim 1, characterized in that: In the step (2), the ultrasonic treatment time is 30 min; the drying temperature is 60° C., and the drying time is 12 h.

5. The method for preparing the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material according to claim 2, characterized in that: In the step (4), the heating rate is 5°C / min.

6. A nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material prepared by the method according to any one of claims 1 to 5.

7. Use of the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material as a catalyst in hydrogen evolution reaction by electrolysis of water as claimed in claim 6.

8. The use according to claim 7, characterized in that: The application method is as follows: dispersing the nitrogen-doped carbon nanosphere@molybdenum carbide@carbon nanotube composite material into a dispersant to obtain a dispersion liquid, applying the dispersion liquid droplets on the surface of a glassy carbon electrode, and drying at room temperature to obtain a working electrode.

9. The use according to claim 8, characterized in that: The dispersant is a naphthol solution.

10. The use according to claim 8, characterized in that: In the hydrogen evolution reaction by water electrolysis, the standard hydrogen electrode is used as the reference electrode and the platinum wire is used as the counter electrode.

Citation Information

Patent Citations

  • Preparation method of multistage structure MoC / N-doped carbon composite microsphere electrode material

    CN108183203A

  • Molybdenum carbide and nitrogen-doped carbon composite material capable of uniformly anchoring platinum single atoms and preparation method of molybdenum carbide and nitrogen-doped carbon composite material

    CN115083786A

  • Preparation method of carbon-coated molybdenum carbide, carbon-coated molybdenum carbide and application of carbon-coated molybdenum carbide

    CN116119669A

Cited By

  • Nanometer flower-shaped three-phase electrocatalyst as well as preparation method and application thereof

    CN120844144A